Infections associated with adventure travel: A systematic review. Issue 16 (March 2017) - Gundacker, Nathan D.; Rolfe, Robert J.; Rodriguez, J. Martin
Abstract: Aim: To review infections associated with adventure travel. Methods: The PubMed, Embase and Scopus databases were searched combining the wordsinfection with the following keywords: rafting, whitewater, surfing, (surfer* or windsurf*), (caves or caving or spelunking), (triathlon or trekking) or (hiking or adventure race), bicycling, backpacking, (mountain climb* or bouldering), horseback riding, orienteering, trekking, and skiing. Results: Adventure travel is becoming much more common among travelers and it is associated with a subset of infectious diseases including: leptospirosis, schistosomiasis, viral hemorrhagic fevers, rickettsial diseases and endemic mycosis. Caving and whitewater rafting places individuals at particular risk of leptospirosis, schistosomiasis and endemic mycosis, while adventure races also place individuals at high risk of a variety of infections including campylobacter, norovirus and leptospirosis. Conclusion: Travel practitioners need to be aware of the risks associated with adventure travel and should educate individuals about the risks associated with various activities. Doxycycline prophylaxis should be considered for travelers who are susceptible to leptospirosis due to participation in high-risk sports such as whitewater rafting, caving or adventure races.